KUALITAS TEGAKAN BENIH LOKAL DI HUTAN LINDUNG KAB. LUWU UTARA - Liana Liana; Witno witno; Hadijah Azis Karim; Arinal Haq (Jurnal Penelitian Kehutanan BONITA, 2021)
Information regarding the potential and dominance of local plant species in the Sassa Village Protection Forest, North Luwu Regency is still limited. In fact, there are fewer and fewer local plant species that are used by the community, this is indicated by the difficulty of obtaining local plant seed sources. This difficulty is due to the lack of local parent plants in this area, for this reason it is necessary to study the potential of local plants and the selection of parent trees for local plant seed sources. The research method by collecting data was carried out using exploratory techniques with the transect method, then the parent tree that had been determined as a seed source stand that had met the criteria as a parent tree was given a coordinate point. Then the scoring was carried out on tree height (T), tree diameter (D), branch-free height (Tbc), trunk straightness (KB), trunk surface (PB) and tree health condition (KK). The results of this study obtained 16 types of plants with the highest T score of 20, 16 species of plants with the highest D score of 30, 33 species that had the highest Tbc score of 15, and 3 types of plants that had the highest KB+PB+KK score of 20. There were 18 species with a total score of 60 that met the highest criteria as well as from the various genotypic characteristics that had been observed.Â